The use of bullock traction technology for crop cultivation in northern Ghana: An empirical economic analysis - Panin, A. (1987)
Assesses the economic impact of bullock traction technology on the farming systems in northern Ghana. Compares the technical and economic aspects of the hand-hoe and bullock traction technology.